COMPENSATION FOR DAMAGES CAUSED BY AUTOMATIC CONTRACTS - Farah Karim Farttoos; Dr. Hassan Fadala Musa (Scholar Express Journals, 2022)
In this research we have treated compensation as an effect of contractual liability that arises when breaching obligations arising from automatic contracts in terms of definition and forms as compensation in kind or monetary and methods of estimating it as judicial, contractual or legal compensation
Keywords: Automatic contracts; Streptococcal liability; Judicial compensation; Agreement compensation